SISTEM INFORMASI RENTAL MOBIL BERBASIS WEB PADA CV MESOY JAYA SENTOSA - Muhammad Gilang Putu Sutrisno, (2023)
In the era of information technology, people can easily access anything, in the car rental process carried out by CV Mesoy Jaya Sentosa, it still uses the konfensional method, customers come directly to the car rental location to make transactions and fill in the customer's personal data konfensionally on paper, with the condition of the company At this time the owner needs a car rental marketing strategy that is able to compete in today's technological developments, the owner must have a medium to reach a wider customer base and be easy to access without having the customer come directly to the car rental location. The right solution for problems that occur is by creating a website-based car rental information sistem that is connected to the internet so that it can make it easier for customers to rent cars and get information regarding car rentals anywhere and anytime. In this study, the researcher used the waterfall method with stages namely needs analysis, design, program code generation, testing, program implementation and maintenance.